Epidemiological Profile of Intestinal Protozoan Infection in Dakar, Senegal: Results from Hospital-Based Survey - Khadime Sylla; Souleye Lelo; Doudou Sow; Cheikh Binetou Fall; Isaac A Manga; Magatte Ndiaye; Babacar Faye; Thérèse Dieng; Roger C.K Tine (Journal of Parasite Research, 2022)
Background Intestinal parasitic infections, especially intestinal protozoan parasites remain significant public health problem in Senegal. Several studies have demonstrated the endemicity of the diseases. The study was carried out with the objective of assessing the epidemiolocal profile of intestinal protozoan infection diagnosed among patients attending to Fann University Hospital in Dakar, Senegal. Materials and Method A retrospective study was conducted from 2016 to 2020. Samples were collected from patients attending to the laboratory for parasitological confirmation. Fresh stool samples were observed using direct examination, formal-ether concentration method and modified Zeilh Nielsen staining method. Descriptive analysis was performed using Stata MP 16 software. The significance level was set at 5%. Results Among 3825 patients selected in the study, 1009 were found with at least one intestinal protozoan parasite representing an overall prevalence of 26.4% (CI 95% (24.7– 28)). Mono-parasitic and di-parasitic infection represent 81.6% and 18.2% respectively while polyparasitism was observed in 26 patients representing 2,6%. Among positive samples, 16 (8.7%) were associated with helminths. Blastocystis sp. (40.8%), Entamoeba Coli (38.2%), Endolimax nana (8.2%) and Giardia intestinalis (8.1%) were mainly observed. Trophozoites Entamoeba histolytica was observed with 2.3%. Frequency of intestinal protozoa was higher in the 15 – 30 age group (28.3%) and in male group (26.9%). The parasite carriage was most important during the wet season comparing the dry season (p = 0.65). Asymptomatic patients (29.5%) were more infected than symptomatic patients (23.5%) (p <10-3). The main clinical symptoms were diarrhea, abdominal pain, dysenteric syndrome, fever, dyspeptic disorders, and vomiting. Conclusion These results showed that intestinal protozoan infections remain prevalent in Senegal with a high proportion of asymptomatic who constitute an important reservoir of parasites. Effective control strategies such as water supply, hands washing, and mass deworming campaign could reduce the prevalence of these diseases.
Keywords: Intestinal Parasite